Peran Pemerintah Daerah Dalam Pemberdayaan Pelaku UMKM di Kota Palopo - Alvira Rahmayanti (Departemen Ilmu Pemerintahan Fisip Unhas, 2024)
The Government's Role in Empowering UMKMs in Palopo City. UMKM activities cover almost all business fields so that the existence of UMKM is very important, especially for increasing income for low-income groups of people. This study aims to find out how the Government carries out its role as a facilitator, as a regulator, and as a catalyst on the 8 indicators mentioned in the Regional Regulations of the City of Palopo, especially in the development of UMKMs in the City of Palopo. The type of this research is qualitative research by explaining events that actually occurred in the field during this research. In this study there were 9 informants consisting of heads of cooperatives and SMEs, 1 head of the UMKM sector, 1 staff of the Cooperatives and UKM Office of Palopo City and several UMKM business actors. Data collection was carried out by direct field observations, interviews and documentation with informants. The results of this study indicate that the government's role in empowering UMKMs is carried out by the Office of Cooperatives and UKM and The City of Palopo in carrying out its role as a Facilitator, Regulator, and as a Catalyst has had a major influence in carrying out the empowerment given so that it can help UMKM actors to maintain and improve their business by providing access to financing and capital, promotion, coaching, mentoring training, and growing the business climate. by looking at the condition of UMKMs, especially micro-type businesses that have grown densely in various areas in Palopo City.